Challenging museum narratives: the case of a Rhodesia Railways carriage - Will Sims; William Law (Science Museum Group Journal)
Science Museum Group (SMG) object 2005-7446 was built by a British rolling stock manufacturer in 1927. It was exported as a first-class passenger coach to British-administered Southern Rhodesia (present-day Zimbabwe) and ran on the lines operated by the former Rhodesia Railways. But, in 1974, the carriage was on its way back to Britain, overseen by the artist, conservationist and railway enthusiast, David Shepherd. After being displayed at a series of locations across Britain, the carriage was acquired by the National Railway Museum, part of SMG, in the early 2000s. It was kept in storage until 2024.